The Role of The Digital Economy in Azerbaijan’s Economic Development - Haciyev, Fuad (PT. EQUATOR SINAR AKADEMIA, 2024)
Azerbaijan is taking important steps towards the digital economy in order to support its economic growth and gain competitive advantage. This article examines the critical role played by the digital economy in the economic development of Azerbaijan. The introduction generally evaluates the economic context of Azerbaijan and emphasizes the importance of the digital economy in this context. The research method section describes the paper's basic data collection and analysis strategies. The Digital Economy and Azerbaijan section defines the basic concepts of the digital economy and examines Azerbaijan's progress in this field. Emphasis is placed on digital economy models and technology integration implemented in the country. The Role of the Digital Economy in Azerbaijan's Economic Development section discusses in detail the effects of the digital economy on economic growth. The role of elements such as innovation, e-commerce, digital finance and banking in the Azerbaijani economy is examined in depth. The Result and Discussion section evaluates the general findings of the article and discusses the potential impacts of the digital economy on the Azerbaijani economy. It also includes various perspectives on predicting future digital economy applications. This article aims to make a significant contribution to the country's efforts to achieve sustainable growth and competitive advantage by highlighting the central role of the digital economy in Azerbaijan's economic development.